Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 511970 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Arthropoda", "Country is Brazil" ] } The dataset includes 511970 records from 277 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0001271-150512124619364/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences